PENGUASAAN LEMBAR KERJA SISWA (LKS) IPA MATERI DAUR ULANG AIR MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LERANING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDIT AL-KHAIR KABUPATEN DELI SERDANG T.A 2019/2020 - Retno Ajeng Widyastri; Vivi Uvaira Hasibuan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2020)
This study aims to determine the characteristics, effectiveness and practicality of CTL based LKS, to improve IPA learning out comes for water recycling materials using the CTL model of class V SD IT Al-khair. This type of research is classroom action research using research methods from Sugiono (2015:409), consisting of several stages, including potential and data collection problems. The subjects of this research were students of class V to Al-khair. The pretes ang posttest experiments were carried out in class V with 24 students. The data analysis technique used descriptive percentage an gain test. Based on validation and material experts, media and teacher. The percentage and content eligibility criteria werw obtained 86,5% (very feasible), 75% presentation feasibility (feasible), and language assessment 85% (feasible), CTL based LKS have an effect on cognitive learning out comes as indicated by the test significance value of 0,000 < 0,5 uni gain of 0,37 with moderate criteria, the percentage of teacher and student responses after the usu of CTL based LKS classically 81,51% positive criteria The conclusion of this research is that the developed LKS with the characteristics of CTL LKS valis improve learning outcomes and are practical for science learning. Suggestions that can be conveyed are CTL based LKS in science learning water cycle material can be used as alternative teaching materials, ini CTL based LKS development it must match the components in CTL, in developing creativity and innovation in order to create interesting student activitiesin LKS.